The religious influence on the availability of paleopathological material in Syro-Palestine - Greeff, C. J. (Journal for semitics, 2006)
This article deals with different aspects of paleopathology. After an overview of the potential value of excavated skeletal material in general. attention is focussed on the religious and political situation in Israel. The influence of Israeli Heritage Laws and the negative role of the ultra-Ortbodox parties on archaeological procedures in Israel are discussed. Finally a review is presented of all the articles in the New Encyclopedia of Archaeological Excavations in the Holy Lond (Ephraim Stem (editor), 1993), as well as a few other cases not included in the Encyclopedia, in terms of their mentioning of excavated human remains and relevant paleopathological information. The conclusion is that alarmingly few reports reflect the excavation of human remains, while significantly less report on paleopathological studies on the bones.